Clinical outcomes of endoscopic retrograde cholangiopancreatography after Billroth II anastomosis: a comparison of gastroscope and duodenoscope - Kang Ho Lee; Gwang Hyo Yim; Jimin Han; Han Taek Jeong (BMC Gastroenterology)
Abstract Background Endoscopic retrograde cholangiopancreatography (ERCP) in patients with Billroth II anastomosis is challenging due to post-surgical anatomical alterations. This study aims to compare the clinical outcomes of using a duodenoscope and a cap-assisted gastroscope in these patients. Methods Seventy-nine patients with Billroth II anastomosis and a naïve papilla were included in the study. ERCP was performed using either a cap-assisted gastroscope (n = 45) or a duodenoscope (n = 34). The primary outcome was the cannulation success rates, while secondary outcomes included clinical success rates, cannulation time, procedure duration, and complications. Results Afferent limb intubation was successful in 67.1% of patients. Among these, selective biliary cannulation (SBC) was achieved in 73.6%, with no significant difference between the two groups. However, cannulation time was significantly longer in the cap-assisted gastroscope group (7.6 min vs. 5.8 min, p = 0.011). Complications occurred only in the cap-assisted gastroscope group, including one perforation (2.2%) and two cases of pancreatitis (4.4%), though the overall complication rate was not significantly different. Among the 40 patients (50.7%) who failed ERCP, percutaneous transhepatic biliary drainage (PTBD) was the most common rescue intervention (55%), followed by other procedures, including percutaneous gallbladder drainage, repeated ERCP, surgery, and conservative treatment. Conclusions Both cap-assisted gastroscopes and duodenoscopes are viable options for ERCP in patients with Billroth II anastomosis. However, cannulation time was significantly shorter in the duodenoscope group.